Retractable syringe - Yi, Lei (2015)
A needlestick injury may pose a high risk of bloodstream infections for anyone if the needle carries HBV, HCV or HIV. Some safety syringe has been patented and been used in some clinics of American and other developed countries to reduce the chance of needlestick. The safety syringes are required to be further developed to make its safety feature more integral and friendly to the users. The student is required to study the design criteria based on the model in Patent US 7476215 B2. Dimensionless analysis are used to satisfy the general syringes with different dimensions. Experiments of different perimeter with different sizes are carried in MATLAB language program. From the results of the experiments, the student can predict the basic trend of the design perimeter, which are pressure, length and mass. Inside pressure and remaining length of the simulated cylinder can be affected by different area, different friction and different mass to be retracted: the inside pressure will increase with less time by increasing the area of the plate, by decreasing the friction between the plunger and the vacuum plunger seal and by decreasing the total retracted mass; the longer retracted length can be achieved by enlarging the plate diameter, by decreasing the friction between the plunger and the vacuum plunger seal and by decreasing the total retracted mass. A simulation based on the results of experiment is made to express the whole retracted process more clearly and visually.